Evolution of Monetary Policy in Peru: An Empirical Application using a Mixture Innovation TVP-VAR-SV Model - Portilla, Jhonatan; Rodríguez, Gabriel (Pontificia Universidad Católica del Perú. Departamento de Economía, 2020)
This paper discusses the evolution of monetary policy (MP) in Peru in 1996Q1-2016Q4 using a mixture innovation time-varying parameter vector autoregressive model with stochastic volatility (TVP-VAR-SV) as proposed by Koop et al. (2009). The main empirical results are: (i) the VAR coefficients and volatilities change more gradually than the covariance errors over time; (ii) the volatility of MP shocks was higher under the pre-Inflation Targeting (IT) regime; (iii) a surprise increase in the interest rate produces GDP growth falls and reduces ináation in the long run; (iv) the interest rate reacts more quickly to aggregate supply (AS) shocks than to aggregate demand (AD) shocks; (v) MP shocks explain a high percentage of domestic variable behavior under the pre-IT regime but their contribution decreases under the IT regime.
Documento de trabajo; 485
Keywords: Monetary Policy; TVP-VAR-SV; Bayesian Estimation; Mixture Innovation Model; Peruvian Economy; http://purl.org/pe-repo/ocde/ford#5.02.00